Drought characterization across agricultural regions of China using standardized precipitation and vegetation water supply indices. (1st September 2021) - Javed, Tehseen; Zhang, Jiahua; Bhattarai, Nishan; Sha, Zhang; Rashid, Sadaf; Yun, Bai; Ahmad, Shakeel; Henchiri, Malak; Kamran, Muhammad
Abstract: Understanding the spatiotemporal dynamics of drought and its potential effect on crop production is critical in decision-making processes to support sustainable food production under climate change. This is especially true for China, the largest producer of cereal crops in the world, where production losses could significantly impact the global food chain. Here, we utilized global remote sensing products to study the spatiotemporal dynamics of meteorological and agricultural droughts across all of China during 1982–2018 and their potential linkage with winter wheat and summer corn yield losses since 2000. Specifically, we derived the agricultural Standardized Precipitation Index (aSPI; at 1, 3, and 6-month scales) and the Standardized Vegetation Supply Water Index (SVSWI) and explored their regional-scale dynamics across four sub-regions of China. Results suggest that the frequency of extreme drought events has increased in China since 2000, mostly affecting the winter wheat growing season (i.e., December–May) across North China. This increased frequency of drought events followed consistent spatiotemporal patterns of 3-month aSPI, mostly affecting Northwest/North China, Qinghai-Tibet, and South China during April, December, and May, respectively. The 3-month aSPI and SVSWI anomalies showed a good correlation with winter wheat yield anomaly across the Qinghai-Tibet area and corn yield across South China. The summer corn yield across all sub-regions and winter wheat yield across some agricultural zones in North China showed significant decreasing trends since 2000. This study provides a useful understanding of the spatiotemporal dynamics of agricultural drought and its potential implications for crop production in China. Graphical abstract: Image 1 Highlights: Precipitation and vegetation index-based drought products were derived for China. Extreme drought and wet event frequency increased over the twenty first century. The winter wheat growing season in the North was mostly affected by drought. Crop yield anomaly showed positive correlation with drought indices. Wheat yield showed increasing (North) and decreasing (South) trends.